A low-emission food system in the Mekong Delta: Trends, policies and practice - Pham, T.T.; Trần, N.M.H.; Nguyễn, T.V.A.; Nguyễn, T.T.A.; Nguyễn, T.V.; Nguyễn, D.T.; Tăng, T.K.H.; Nguyễn, D.Y.K.; Nguyễn, T.S.; Trần, V.N. (CIFOR-ICRAF, 2023)
This report provides an overall picture of the policy-oriented and practical stakeholders involved in implementing policies and programs related to low-emission food systems in the Mekong Delta - the center Vietnam’s largest food producer and supplier. The report is based on a review of the legal and policy framework, decisions of the Government of Vietnam, secondary documents and opinions shared by experts in the national consultation workshop. The report also identifies opportunities and challenges for building and implementing low-emission food systems in this region.